Which serum uric acid levels are associated with increased cardiovascular risk in the general adult population? - Krajčoviechová, Alena; Wohlfahrt, Peter; Bruthans, Jan; Šulc, Pavel; Lánská, Věra; Eremiášová, Lenka; Pudil, Jan; Linhart, Aleš; Filipovský, Jan; Mayer, Otto; Widimský, Jiří; Blaha, Milan; et al. (Journal of clinical hypertension (Greenwich, Conn.), 2020)
Our aim was to determine the serum uric acid (SUA) levels associated with an increased risk of cardiovascular (CV) and all-cause death in the general adult population. We analyzed data obtained in two independent cross-sectional surveys performed in the Czech Republic in 2006-09 and 2015-18, involving 1% population random samples in nine districts, aged 25-64 years, stratified by age and gender. Ten-year mortality data were obtained in a cohort with examination in 2006-09. Final analyses included 3542 individuals (48.2% men) examined in 2006-09, and 2304 (47.4% men) examined in 2015-18. From a cohort examined in 2006-09, 122 men and 60 women were reported dead (33% and 27% from CV disease). In men, there was no association of baseline SUA levels with baseline SCORE category or 10-year mortality rates. In women, each 10 µmol/L increase in baseline SUA levels was associated with an increase in baseline SCORE category (P < .001). Receiver operating characteristic curve analyses in women identified the baseline SUA cutoff values discriminating: 1. between low/intermediate and high/very high SCORE categories (309 µmol/L), 2. CV mortality (325 µmol/L), and 3. all-cause mortality (298 µmol/L). After adjusting for confounders including SCORE, Cox regression analysis confirmed that the baseline SUA cutoffs of 309 µmol/L and 325 µmol/L were associated with 4-times (P = .010) and 6-times (P = .036) greater risk of CV mortality, whereas the cutoff of 298 µmol/L was associated with 87% greater risk of all-cause mortality (P = .025). In conclusion, the SUA cutoff value of 309 µmol/L identified women at high/very high SCORE category and was associated with 4-times greater risk of observed CV mortality over 10 years.
Keywords: uric acid; Uric Acid; kardiovaskulární nemoci; risk; Humans; lidé středního věku; cardiovascular; rizikové faktory kardiovaskulárních chorob; Female; rizikové faktory; dospělí; lidé; kyselina močová; Adult; ženské pohlaví; Cardiovascular Diseases; SCORE; Male; Middle Aged; Heart Disease Risk Factors; gender differences; Cross-Sectional Studies; mužské pohlaví; průřezové studie; Risk Factors